A review of the Oriental Campeprosopa species (Diptera: Stratiomyidae) - Mason, Franco; Rozkošný, Rudolf (Zootaxa, 2008)
The Oriental species of Campeprosopa Macquart are re-examined based on material (149 specimens) from 9 institutions worldwide. Special attention was focused on the taxonomic value of diagnostic characters and variability of individual species. A thorough revision resulted in discovering four new synonyms of C. flavipes Macquart, 1850: C. munda OstenSacken, 1881, syn.nov.; C. bella Edwards, 1919, syn.nov.; C. ornata Edwards, 1919, syn.nov.; C. pulchra Edwards, 1919, syn.nov. Lectotypes were designated for Campeprosopa munda and Ampsalis longispina Brunetti, 1913. According to present knowledge, the distribution of three valid species seems to be allopatric. The distribution area of C. borneensis Lindner, 1937 is very probably confined to the Malaysian part of Borneo, while C. flavipes occupies the southernmost part of Thailand and entire Sumatra and Java and C. longispina (Brunetti, 1913) occurs in eastern India and northern Thailand and Laos.